Lysosome-Associated Membrane Protein Targeting Strategy Improved Immunogenicity of Glycoprotein-Based DNA Vaccine for Marburg Virus - Xiyang Zhang; Yubo Sun; Junqi Zhang; Hengzheng Wei; Jing Wang; Chenchen Hu; Yang Liu; Sirui Cai; Qinghong Yuan; Yueyue Wang; Yuanjie Sun; Shuya Yang; et al. (Vaccines)
Marburg hemorrhagic fever (MHF) is a fatal infectious disease caused by Marburg virus (MARV) infection, and MARV has been identified as a priority pathogen for vaccine development by the WHO. The glycoprotein (GP) of MARV mediates viral adhesion and invasion of host cells and therefore can be used as an effective target for vaccine development. Moreover, DNA vaccines have unique advantages, such as simple construction processes, low production costs, and few adverse reactions, but their immunogenicity may decrease due to the poor absorption rate of plasmids. Lysosome-associated membrane protein 1 (LAMP1) can direct antigens to lysosomes and endosomes and has great potential for improving the immunogenicity of nucleic acid vaccines. Therefore, we constructed a DNA vaccine based on a codon-optimized MARV GP (ID MF939097.1) fused with LAMP1 and explored the effect of a LAMP targeting strategy on improving the immunogenicity of the MARV DNA vaccine. ELISA, ELISpot, and flow cytometry revealed that the introduction of LAMP1 into the MARV DNA candidate vaccine improved the humoral and cellular immune response, enhanced the secretion of cytokines, and established long-term immune protection. Transcriptome analysis revealed that the LAMP targeting strategy significantly enriched antigen processing and presentation-related pathways, especially the MHC class II-related pathway, in the candidate vaccine. Our study broadens the strategic vision for enhanced DNA vaccine design and provides a promising candidate vaccine for MHF prevention.